Duterte and Alliance Behavior of the Philippines - Taylor Alexis Rodier (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2022)
Many have defined the Philippines' dominant alliance behavior to be hedging; that is, an alignment choice adapted to address the security challenges often faced by small and middle powers in relation to major powers. Hedging should be understood as a strategy to manage the security risks that small and middle powers face, whereas balancing and bandwagoning are security strategies created in response to security threats. This paper argues that before President Duterte's election in 2016, it could be argued that the Philippines was engaging in hedging or low intensity balancing between the U.S. and China. However, Philippine foreign policy underwent a swift about-face as a result of Duterte's objectives, and as a result the country began bandwagoning with China.